An Analysis of Writing Strategies Used by Students of English Language Department - Retno Wulan Dari; Eva Rahmawati; Suvi Akhiriyah (Journal of Languages and Language Teaching, 2022)
The trend towards more process-oriented academic writing instructions require students to pay more attention to and develop their use of writing strategies to ensure learning success. Accordingly, the current study investigates the use of writing strategies performed by freshmen of the English language department in an Indonesian teaching university. The study is an initial effort to provide a theoretical basis for the development of more student-centered and process-oriented writing instructions for the university’s academic writing courses. To attain its purpose, the study focuses its investigation into the stage where writing strategies are most likely to be used and the types of writing strategies being employed by students. Questionnaires modified from Petrić & Czárl (2003) were distributed to 125 freshmen to obtain the data which constitute the types of writing strategies being used, their frequency of use, and the stages of writing within which they were used. Descriptive quantitative analysis was performed afterwards to the collected data. Results show that most freshman are medium users of the strategies, with While Writing as the stage within which students tend to use writing strategies, followed by Pre-writing and Revising Writing. This result implies that the development of learning instruction for academic writing needs to accommodate the development of writing strategies used in three stages of writing, particularly during the Pre-writing and Revising Writing. Further research is also required with different data collection method and instruments to allow for generalization to wider audience which is not possible with the current research, given its limited use of instrument and participants involved.